2008
DOI: 10.1093/ejechocard/jen026
|View full text |Cite
|
Sign up to set email alerts
|

Prolapsing left atrial myxoma: preoperative diagnosis using a multimodal imaging approach with magnetic resonance imaging and real-time three-dimensional echocardiography

Abstract: According to the guidelines of the European Society of Cardiology on the diagnosis and management of pericardial diseases, tissue Doppler imaging (TDI) is proposed to be part of the diagnostic work-up in patients with suspected constrictive pericarditis (CP). We describe a case which illustrates that TDI analysis may be misleading in patients with severe pericardial calcifications of the lateral mitral annulus. Multi-slice computed tomography (MSCT) data in this case contributed much to a better understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Myxomas can occur in hereditary syndromes, but 93% are nonhereditary myxomas. Typically, patients are referred to echocardiography after a cerebral or peripheral embolic event; in rare cases, patients show clinical signs of valvular obstruction [35] which can be verified by color Doppler as demonstrated in the example of a giant left atrial myxoma shown in . Fig.…”
Section: Primary Benign Cardiac Tumors J Myxomamentioning
confidence: 99%
See 3 more Smart Citations
“…Myxomas can occur in hereditary syndromes, but 93% are nonhereditary myxomas. Typically, patients are referred to echocardiography after a cerebral or peripheral embolic event; in rare cases, patients show clinical signs of valvular obstruction [35] which can be verified by color Doppler as demonstrated in the example of a giant left atrial myxoma shown in . Fig.…”
Section: Primary Benign Cardiac Tumors J Myxomamentioning
confidence: 99%
“…Usually connected to the endocardium by a pedicle, myxoma can also occur with a broad base. RT3DE has been demonstrated to provide accurate anatomic visualization as well as improved identification of the spatial relation of a myxoma to the interatrial septum [35][36] [37]. Butz et al [35] described an improvement in evaluation of obstructive effects on ventricular in-or outflow by using RT3D TEE.…”
Section: Primary Benign Cardiac Tumors J Myxomamentioning
confidence: 99%
See 2 more Smart Citations
“…To prevent such complications, tumor identification and surgical excision are essential. The prolapsing of the tumor into the left ventricular outflow tract with consecutive obstruction is a very rare finding [5,6]. The echocardiographic findings should be confirmed by histopathology, because of several clinical differential diagnoses including myxoma, lipoma, vegetation, and thrombi.…”
mentioning
confidence: 96%